VD_FINDINFO HC / 2012 / 276 vom 20. April 2012 - VD Tribunal cantonal (2012)
RESPONSABILITÉ DES ORGANES DE LA TUTELLE, PRESCRIPTION | 454 al. 1 CC, 60 al. 1 CO, 60 CO, 153 CPC, 319 let. b ch. 2 CPC (CH)